Die Entwicklung der ungelenkten Agrarkolonisation im Grenzgebiet von Ghana und der Elfenbeinküste - Schaaf, Thomas; Manshard, Walther (ERDKUNDE, 1988)
Although Ghana and the Ivory Coast are endowed with comparable natural resources, the two countries have experienced a different economic development since their political independence. The Ivory Coast pursued a strategy of economic diversification. Apart from cocoa production which had been the leading cash crop during the colonial period, a strong emphasis has been laid on the production of coffee, oilpalms, coconuts, and citrus.One of the causes for Ghana's economic decline has been the neglect of diversifying the economic structure, which starting in the colonial period, is primarily based upon cocoa production. The economy's monostructure made the country vulnerable to external world market price fluctuations. Within the forest zone, pioneer setlements were founded by migrant farmers for cocoa production in Ghana, and cocoa and coffee production in the Ivory Coast. For easier penetration into the forest, the spontaneous settlers have often followed roads constructed by timber companies. While the plantations lie within the forest, the villages are located right at the road for easier and more rapid access to urban and semi-urban markets. As a consequence of destroying the forest, the primary forest of the two countries degenerated into an ecologically fragile secondary forest with only low economic value for timber production. This paper analyzes the effects of spontaneous agricultural colonization on settlements and land use patterns under the influence of different socio-economic developments during the last decades. In Ghana and Ivory Coast pioneer farmers and their families have moved further into the forest belt during the last decades clearing land both for commercial agriculture (especially cocoa) and for subsistence agriculture. The adjoining savannah zone has been a region of outward migration both into the towns of the South and into the hitherto rather underpopulated West African Middle Belt.